Comportamento de cultivares de cafeeiro em diferentes densidades de plantio - Paulo, Edison Martins [UNESP]; Furlani Junior, Enes [UNESP]; Fazuoli, Luiz Carlos (FapUNIFESP (SciELO), 2005)
This experiment was developed at Adamantina, west region of the State of São Paulo, Brazil, during May 1995 to June of 2000. The plant growth and productivity of two coffee cultivars Catuaí Amarelo IAC 47 and Obatã IAC 1669-20, were evaluated considering to plant densities of 2.500, 5.000, 7.519 and 10.000 plants ha-1. The density of 2500 also was studied with two plants in the same hole, spaced of 2,0 m in the plant line. The experimental design was the randomized completely blocks with three replications, using the split-plot system. The plots were the densities and the split-plots were the cultivars. Results showed that, with increasing of the planting density, the plant height also increased, while the stem and plant basis diameters were reduced, however the planting density did not affect the height of the first branch. The increase of the planting density also increased the field productivity and reduced the production of individual plant. The cultivation of two plants at the same hole reduced the stem diameter and the plant yield. The cultivar Catuaí Amarelo IAC 47 showed the higher plant height and the higher plant basis diameter while cv. Obatã IAC 1669-20 showed the higher stem diameter. The field productivity and individual plant productivity were not different between those cultivars in the period studied (1997-2000).
The behavior of coffee cultivars under different plant densities
Keywords: Coffea arabica L.; Coffee; Competition; Density of the plants; coffee; competition (ecology); population density; yield; Brazil; Sao Paulo [Brazil]; South America; Western Hemisphere; World; Coffea arabica; Embryophyta